2021
DOI: 10.23736/s1973-9087.21.06692-2
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of robotic rehabilitation on balance and gait outcomes in people with multiple sclerosis? A systematic review of randomized control trials

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Although robotic rehabilitation effects on balance and gait have been recently investigated with positive results in patients with MS (54), few studies in literature addressed the effectiveness of VR and exergames compared with conventional treatment in patients with MS and in most cases only considering VR as a complementary tool in MS rehabilitation concerning balance. This could be related to the relative novelty of these devices and the difficult implementation in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although robotic rehabilitation effects on balance and gait have been recently investigated with positive results in patients with MS (54), few studies in literature addressed the effectiveness of VR and exergames compared with conventional treatment in patients with MS and in most cases only considering VR as a complementary tool in MS rehabilitation concerning balance. This could be related to the relative novelty of these devices and the difficult implementation in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…1 Another important aspect to consider before we start the widespread use of exoskeletons in MS relates to the specific patient subgroup that may benefit. Indeed, it is suggested that clinical effects of robot-assisted gait training are superior to conventional treatment in severely (but not in moderately) affected people with MS. 1,2 These results were implemented in the figure published by Calabro et al, 3 where patients gait deficits (based on Expanded Disability Status Scale (EDSS) scores) were plotted relative to the type of the therapy and devices (from overground walking training to powered exoskeletons to grounded exoskeletons).…”
mentioning
confidence: 99%
“…7 It is known that adding virtual reality during rehabilitation can be useful to promote neuroplasticity and recovery in persons with MS, increasing subjects' motivation and compliance. 2 Combination of exoskeleton therapy with virtual reality, can increase the impact on motor and non-motor outcomes such as psychological well-being and quality of life. 3,8 Third, although there is progress related to the usability of exoskeletons there is still a lot of improvement possible.…”
mentioning
confidence: 99%
“…Robot-assisted gait training (RAGT) has been introduced into clinical practice to overcome these limitations and deliver task-oriented, high-intensity gait rehabilitation [12,13]. The efficacy of RAGT among PwMS has been recently reviewed [14,15], and this intervention has been promoted as an option for severely disabled PwMS. Despite the evidence of its clinical efficacy, however, little information is available on the mechanisms underlying the recovery or brain reorganization processes that occur after RAGT.…”
Section: Introductionmentioning
confidence: 99%